MENIMBANG KEMBALI KONSEP DAN GERAKAN FUNDAMENTALISME ISLAM DI INDONESIA - Basyir, Kunawi (AL-TAHRIR, 2014)
Studies on religious fundamentalism has re-drawn a serious attention from scholars after the ascalation of a series of religious violence in the name of religion, including in Indonesia. Several theories of political radicalization have been formulated. These theories ironically exert serious implication of stigmatization and over-generalization to Muslims in many parts of the world who have nothing to do with fundamentalist and radical Islam. This article attempts to problematize those theories and concepts of Islamic fundamentalism in Indonesia. This article argues that the definition of Islamic fundamentalism that many scholars have formulated do not work properly. The Indonesian discourses show that Islamic fundamentalism is often seen as movements or thoughts that respond and criticize the ideology of Islamic modernism. A common theory of Islamic fundamentalism in Indonesia divides Islamic fundamentalism into two kinds, namely radical fundamentalism such as Front Pembela Islam, and soft fundamentalism such as Hizbut Tahrir Indonesia and Majelis Mujahidin Indonesia. However, similarities between these two kinds of movement in terms of their views on secularization and democracy are ample so that such s definion is misleading.Keywords: concept of fundamentalism, radical fundamentalism, peaceful fundamentalismÂ Â